Nietzsche versus Nietzsche or on Nietzsche - Fogel, Gilvan; Ortíz, Carlos (Estudios de Filosofía, 1991)
This text has to do with thought as fashion; specifically, the Nietzsche fashion. Nihilism is considered in a double meaning: on the one hand it constitutes our origin, our genesis, and on the other this nihilism is a correlative of fashion (in thought). A true philosophy is essentially outmoded, extemporaneous. Thevertiginous striving after what is in fashion has to be opposed by a search of lentitude